Basic Views of School-Based Management Theory in Improving Education Quality - Aminah, Lilik; Mukarromah (Adabuna : Jurnal Pemikiran dan Pendidikan, 2023)
The main role of education is to improve the quality of human resources, both through government and non-government institutions. One solution is through School Based Management (SBM) as a management of resources to improve the quality of education. Schools are given direct authority regarding services in schools both internally and externally. This is in line with the decentralization policy which encourages schools to make decisions in a transparent, accountable and participatory manner by involving school members such as principals, teachers, students, parents and the community.